The birds at my table : why we feed wild birds and why it matters - Jones, Darryl N. (Comstock Publishing Associates, an imprint of Cornell University Press, 2018)
"Discusses the history and scale of feeding wild birds. Outlines debates about the practice, highlighting key research findings and pointing out the issues that require further examination. Written in nontechnical language, thus making it accessible to the general public, birders, and academics"--